SUITABILITY LOCATION FOR INCLUSIVE HIGH SCHOOL IN BEKASI CITY WEST JAVA PROVINCE BASED ON SCHOOL CAPACITY - Hasanah, Galuh Izma; Nurlambang, Triarko; Zulkarnain, Faris (UI Scholars Hub, 2021)
The development of inclusive education provider school must also be supported by the provision of good and optimal education facilities. In this study an evaluation was conducted on senior high school (SMA) located in three (3) sub-district areas in Bekasi City, namely Kecamatan Medan Satria, Kecamatan Jatiasih , and Kecamatan Bekasi Utara. These three areas were selected based on the percentage of the availability of the highest educational facilities in Bekasi. The Determination of location was chosen based on consideration through the site of school capacity variables based on the quantitative method. The results showed school characteristics can be seen as quality of the capacity for each school. In this study, it can be seen that schools can accommodate 1-7 study groups on average, the proportion of facilities and infrastructure for children with special needs reaches 55.5%. The research showed that the calculation of school's capacity resulted in 20% of total number of schools in suitable criteria, 27% of schools that were in moderately suitable criteria, 50% were in less suitable criteria, and only 3% of schools were in marginally suitable criteria